Failure of commercial extruded catalysts in simple compression and bulk thermal cycling. Issue 1 (21st August 2017) - Young, Alice; Henderson, Sam; Buchanan, Liam; Hall, Daniel; Bishop, Catherine
Abstract: The mechanical performance of three commercial extruded catalyst pellets was characterized by single particle compression testing in five orientations and bulk crush testing during thermal cycles from 20°C to 900°C in a reformer tube. Failure loads were analyzed with Weibull statistics, and fragment shapes were cataloged. Maximum principal stresses from finite element simulations were consistent with the shapes of fragments from single pellet tests. In smaller scale bulk tests, excluding pellets in contact with the top and bottom plates, the most common location of damaged pellets was in contact with the reformer wall. In one large‐scale test (280 pellets), damage was most common in pellets at the reformer wall. The most common fragment shapes from ex‐service single pellet tests and bulk tests are similar, but differ from those from single pellet tests. Neither single pellet compression testing nor conventional bulk crush testing is a sufficient analog for the loading conditions on catalyst pellets in reformer tubes. This study demonstrates that catalyst pellet damage occurs in each full thermal cycle, and that using thermal cycling to reproduce the boundary conditions in service is essential for future studies.